Prospek Pengaturan Olahraga Elektronik dalam Undang-Undang Sistem Keolahragaan Nasional - Kevin Ali Rakhmadi; Aan Efendi; RA Rini Anggraeni (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
In principle, sports are carried out physically in gyms and fields, which are often done by the public. However, nowadays, with the progress and development of technology, sports can be done not physically and sweating, but simply with intelligence and technological sophistication, for example online games. In such sports, the existing regulations are not yet able to regulate it in its entirety so that if there is a violation of the online game protocol there is no clear legal payment as a reference in providing and making legal decisions. The existing Sports Law, namely Law 11/2022, does not yet accommodate this, so clear concepts and laws are needed to avoid a legal vacuum. The research results require the existence of a clear legal format to regulate and at the same time limit online games, which have been subject to many violations and restrictions. In conclusion, there is a need to revise and update regulations relating to sports in relation to technology.